2019
DOI: 10.1017/cem.2019.435
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce emergency department consultation time: A systematic review of the literature

Abstract: ObjectivesOvercrowding in the emergency department (ED) is associated with increased morbidity and mortality. Studies have shown that consultation to decision time, defined as the time when a consultation has been accepted by a specialty service to the time when disposition decision is made, is one important contributor to the overall length of stay in the ED.The primary objective of this review is to evaluate the impact of workflow interventions on consultation to decision time and ED length of stay in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Secondly, we should increase the number of doctors and give each patient enough time to visit. Until the outbreak of the epidemic, doctors in the capital cities of provinces were only able to see patients for 3–5 min, and the amount of time individuals were allowed to see a patient was diminished considerably ( 38 ). After the outbreak of COVID-19, doctors have become more difficult to interview.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we should increase the number of doctors and give each patient enough time to visit. Until the outbreak of the epidemic, doctors in the capital cities of provinces were only able to see patients for 3–5 min, and the amount of time individuals were allowed to see a patient was diminished considerably ( 38 ). After the outbreak of COVID-19, doctors have become more difficult to interview.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Others have shown improvements in consult response time and LOS by implementing structures around communication. 6 , 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews assessing interventions to improve ED throughput have generally not focused on the impact of interventions targeting the ED consultation process 8,9 . One previous systematic review reported that interventions aiming to reduce consultation to decision time were generally effective; however, the methodological quality of the available studies was poor, the review is dated, and new evidence could clarify their impact on practical measures of ED throughput 5 . The objective of this systematic review was to describe and evaluate the effectiveness of interventions aiming to improve the ED consultation process.…”
Section: Introductionmentioning
confidence: 99%
“…1 Research shows that increased ED LOS results in decreased patient satisfaction, increased hospital admissions, and increased mortality. 3,4 Various types of interventions impacting the specialist consultation process, including reducing wait times for responding and completing consultations, 5 early identification of patients most likely requiring consultation, 6 and limiting unnecessary consultations, have been thought to improve ED throughput and reduce overcrowding. 7 The overall effectiveness of ED-based interventions that specifically influence the consultation process, however, is not well understood.…”
Section: Introductionmentioning
confidence: 99%